An Analysis of Relationship between Stock Futures and Underlying Stock Volatility - Ganai, Dr. Khurshid Ali (Archives of Business Research, 2020)
In this study, the researcher has undertaken an analysis to establish whether the introduction of stock futures trading influences the volatility of the underlying stock or not. In order to establish this, the researcher has taken eight companies into consideration which belongs to four different sectors such as pharmaceuticals, Banking, Oil and Gas and Fast Moving Consumer Goods sector. The researcher has taken a reference period of fourteen years which is sub-divided into two sub-groups namely pre-derivatives period, comprises of seven years from 1995-2001 and post-derivatives period, comprises of seven years from 2002-2008. The findings put forth by the study confirms increased volatility during the post-derivatives period compared to pre-derivatives period. These findings collaborates with the findings of Lee and Oak (1992), Bechetti and Robert (1999) and Kamara et.al (1992).